Spontaneous lymphoproliferation differentiates two groups of HTLV-1 asymptomatic carriers: with and without high cell proliferation and death - Marta de Souza Porto; Tatiana Mitiko; Victor Folgosi; Dewton Vasconcelos; Mauricio Domingues; Michel Haziot; Jerusa Smid; Rosa Marcusso; Youko Nukui; Augusto C. P. Oliveira; Tatiane Assone; Jorge Casseb; et al. (Immunologic Research, 2026)
HTLV-1 infection causes chronic immune activation and a prolonged asymptomatic phase, but the functional features that define early disease remain unclear. We evaluated whether spontaneous proliferation (SP) and related functional immune parameters can distinguish clinical stages across the HTLV-1 spectrum. Spontaneous and mitogen-induced lymphoproliferation (PHA, anti-CD3), measured by CFSE dilution, and in vitro cell death, measured by cytometry, were assessed in 435 HTLV-1-infected individuals: asymptomatic carriers (AC, n = 303), individuals with intermediate syndrome (IS, n = 21), patients with HTLV-1-associated myelopathy (HAM, n = 94), adult T-cell leukemia/lymphoma (ATL, n = 17), and two control groups. Notably, SP levels divided the asymptomatic individuals in two subgroups: low-SP (24.5%), similar to the control groups, and high-SP (75.5%), resembling IS, HAM, and ATL patients. Additionally, high-SP AC and HTLV-1 symptomatic groups showed significantly reduced responses to PHA and increased spontaneous and PHA-stimulated cell death, all features also observed in IS, HAM, and ATL patients, while low-SP AC results mirrored those of control groups. This increased cell death is strongly correlated with upregulation of Fas and FasL, especially in lymphocytes from high-SP AC, which may underlie the chronic activation and susceptibility to cell death. These findings suggest that HTLV-1 AC comprises two distinct subgroups: one with high SP and cell death, likely due to ongoing viral activity and immune alterations, and another with low SP, low viral activity, and preserved immune homeostasis. Follow up studies of AC with these functional changes are needed to determine if they can help monitor disease progression and identify asymptomatic individuals at higher risk of clinical deterioration.